2010
DOI: 10.1021/ac100550c
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Proteins and Protein−Ligand Complexes Using HgTe Nanostructure Matrixes in Surface-Assisted Laser Desorption/Ionization Mass Spectrometry

Abstract: We have analyzed peptides, proteins, and protein-drug complexes through surface-assisted laser desorption/ionization mass spectrometry (SALDI-MS) using HgTe nanostructures as matrixes. We investigated the effects of several parameters, including the concentration of the HgTe nanostructures, the pH of the buffer, and the concentration of salt, on the performance of this system. When HgTe nanostructures are used as matrixes, [M + H](+) ions were the dominant signals. Relative to other commonly used nanomaterials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 43 publications
1
63
0
1
Order By: Relevance
“…Besides, the improved harnessing of nanomaterial production processes allowed well-controlled inorganic matrix preparation from metals, metal oxides and alloys, under different frameworks. For instance gold [14], iron [15], silver [16], platinum [17], cobalt [18], titanium [19] and other elements [20][21][22][23][24], alone or in combination, were investigated as inorganic matrices by several research groups worldwide. Moreover, disposable ready-to use LDI nanostructured surfaces can be purchased like Nano-Assisted Laser Desorption/Ionization (NALDI™) target plates, constituted by silylated silicon nanowires, which were recently developed for 'matrix-free' LDI analysis of small molecules [25].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the improved harnessing of nanomaterial production processes allowed well-controlled inorganic matrix preparation from metals, metal oxides and alloys, under different frameworks. For instance gold [14], iron [15], silver [16], platinum [17], cobalt [18], titanium [19] and other elements [20][21][22][23][24], alone or in combination, were investigated as inorganic matrices by several research groups worldwide. Moreover, disposable ready-to use LDI nanostructured surfaces can be purchased like Nano-Assisted Laser Desorption/Ionization (NALDI™) target plates, constituted by silylated silicon nanowires, which were recently developed for 'matrix-free' LDI analysis of small molecules [25].…”
Section: Introductionmentioning
confidence: 99%
“…The upper detected mass limits using various NP matrices are generally below 26 kDa for protein samples and 7 kDa for polymers [34,58]. A HgTe NP matrix was reported to increase the upper mass limit for proteins to 150 kDa [59]. A nanostructure initiator development study involving instant release of the trapped initiator molecules (e.g., 14 kDa poly(3,3,3-trifluoropropylmethylsiloxanes) from silicon pores expanded the protein mass detection range to 30 kDa [60].…”
Section: Npca Maldi Ms Of High Mass Pdmsmentioning
confidence: 99%
“…Other inorganic materials are also used to assist LDI, such as graphite [33], carbon nanomaterials [34][35][36], nanodiamonds [37], porous alumina [38], nano-ZnO [39,40], EuF 3 hollow hexagonal nanodisks [41], silver nanoparticles [42], HgTe nanostructures [43], platinum nanoflowers [44], manganese oxide nanoparticles [45], Fe 3 O 4 particles [46], fullerene-derivatized silica [47] and germanium nanodots [48], among others. Recently, we have shown that quantum dots (QDs) of cadmium selenide and cadmium selenide covered with cadmium sulfide can also be used to assist LDI [49].…”
Section: Nanomaterial-assisted Laser Desorption Ionizationmentioning
confidence: 99%